Dietary Flaxseed Reduces Central Aortic Blood Pressure Without Cardiac Involvement but Through Changes in Plasma Oxylipins. Issue 4 (October 2016) - Caligiuri, Stephanie P.B.; Rodriguez-Leyva, Delfin; Aukema, Harold M.; Ravandi, Amir; Weighell, Wendy; Guzman, Randolph; Pierce, Grant N.
Abstract : In the year-long FlaxPAD clinical trial (Flaxseed for Peripheral Artery Disease), dietary flaxseed generated a powerful reduction in brachial systolic and diastolic blood pressure in patients with peripheral artery disease. Oxylipins were implicated as potential mechanistic mediators. However, the ability of flaxseed to impact central aortic hypertension, arterial stiffness, or cardiac performance was not investigated. Additionally, the relationship between central blood pressure (cBP) and oxylipins was not elucidated. Therefore, radial tonometry and pulse wave analysis were used to measure cBP and cardiac function in the FlaxPAD population (n=62). Plasma oxylipins were analyzed with high-performance liquid chromatography mass spectrometry. In patients with high blood pressure at baseline, the average decrease in central systolic and diastolic blood pressures versus placebo was 10 and 6 mm Hg, respectively. Flaxseed did not significantly impact augmentation index or other cardiac function indices. Alternatively, the data support several specific oxylipins as potential mediators in the antihypertensive properties of flaxseed. For example, every 1 nmol/L increase in plasma 16-hydroxyeicosatetraenoic acid increased the odds of higher central systolic and diastolic blood pressures by 12- and 9-fold, respectively. Every 1 nmol/L increase in plasma thromboxane B2 and 5, 6-dihydroxyeicosatrienoic acid increased the odds of higher cBP by 33- and 9-fold, respectively. Flaxseed induced a decrease in many oxylipins, which corresponded with a reduced risk of elevated cBP. These data extend the antihypertensive properties of flaxseed to cBP without cardiac involvement but rather through oxylipins. This study provides further support for oxylipins as therapeutic targets in hypertension. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00781950. Abstract : Supplemental Digital Content is available in the text.